Ubezpieczenia skierowane do muzułmanów - wyzwanie dla współczesnych rynków finansowych - Łyskawa, Krzysztof; Wojtkowiak, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Because of lack of separation of the secular and religious principles in many Islamic countries, there is need to create insurance products in compliance with Sharia law. It causes that the solutions are not allowed to include elements of: 1 ) uncertainty (gharar), 2) gambling (moisir), 3) interest (riba). The development of Islamic insurance (takaful) and banking indicates that Muslim communities need the financial services. In the Polish insurance market, conception of takaful can be realized by properly formed and managed mutual insurance companies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 242-252